PENGARUH GAJI TERHADAP KETERAMPILAN MENGAJAR (STUDI PADA SMA KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR RIAU) - Sari, Wardani Purnama (Universitas Batanghari Jambi, 2018)
Abstract This research aims to analyze the effect of salary on teaching skills. The population of this research is the private high school teachers throughout the District of Rokan Hilir Bagan Sinembah totalling 137 persons. Sample with drawal technique with random sampling with propotional amount of samples as many as 135 people. Engineering data collection used by providing questionnaires. The data collected are then analyzed using statistics structure equation models. The results showed that the salary effect significantly to teaching skills.Keyword : Salary, Teaching Skills.